Clinical and post-mortem signs in European wild boars and domestic pigs infected with African swine fever virus - S. G. Remyga; A. S. Pershin; I. V. Shevchenko; A. S. Igolkin; A. A. Shevtsov (Ветеринария сегодня)
The paper covers comparative assessment of clinical and postmortem signs in wild boars and domestic pigs infected with one and the same epizootic isolate of African swine fever virus. In addition, a model has been developed to demonstrate the disease spread under conditions comparable to those on a pig farm. Based on the obtained results two infectious doses 50 and 5000 H AU/head were chosen for infecting the animals with «Shikhobalovo 10/13» isolate of African swine fever virus. When infecting the animals with the abovementioned isolates both wild boars and domestic pigs demonstrated similar clinical and postmortem signs typical for acute form of African swine fever.